1992
DOI: 10.1021/jm00091a005
|View full text |Cite
|
Sign up to set email alerts
|

Electrophilic opioid ligands. Oxygen-tethered .alpha.-methylene-.gamma.-lactone, acrylate, isothiocyanate, and epoxide derivatives of 6.beta.-naltrexol

Abstract: O6-Ether derivatives of 6 beta-naltrexol in which the ether substituent includes various electrophilic groups have been synthesized in an effort to examine structure-activity requirements at the 6 beta-substituent for receptor affinity and irreversibility of binding in opioid receptor preparations. A series of tethered 6 beta-ethers having terminal epoxides, alpha-methylene-gamma-lactones, and an isothiocyanate group were prepared. The stereochemistry of the alpha-methylene-gamma-lactones was established by co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1995
1995
2004
2004

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…After conditioning the silica gel with CH2Cl2 (100 mL), the residue was eluted sequentially with CH2CI2 (150 mL), 80:20 CH2Cl2:EtOAc (300 mL), and 50:50 CH2Cl2:EtOAc (200 mL). The product was eluted with the second eluent mixture, and removed of solvent by rotary evaporation afforded 20 as a yellow foam (390 mg, 63% yield): NMR (CDCls) ó 8.03 (d, J = 8.2 Hz, 1 H, C-24 H), 7.98 (d, J = 8.2 Hz, 1 H, C-27 H), 7.52 (dd, J = 7.6, 7.6 Hz, 1 H, C-26 H), 7.39-7.47 (m, 6 H, C-23' 3 H, C-27' 3 H), 7.33 (dd, J = 7.8, 7.8 Hz, 1 H, C-25 ), 7.12-7.26 (m, 9 H, C-24' 3 H, C-25' 3 H, C-26' 3 H), 6.47 (d, J = 8.2 Hz, 1 H, C-2 H), 6.22 (d, J = 8.3 Hz, 1 H, C-l ), 5.09 (d, J = 15.5 Hz, 1 H, C-21 H), 5.01 (d, J = 15.2 Hz, 1 H, C-21 H), 4.45 (d, J = 6.4 Hz, 1 H, C-5/3 ), 3.10-3.22 (m, 1 H, C-6a H), 2.99 (d, J = 4.9 Hz, 1 H, C-9 H), 2.86 (d, J = 18.6 Hz, 1 H, C-10/3 H), 2.37-2.55 (m, 2 H, C-lOa H, C-16 H), 2.29 (d, J = 6.5 Hz, 2 H, C-17 2 ), 1.72-2.12 (m, 4 H, C-7 2 H, C-15 H, C-16 ), 1.48-1.59 (m, 1 H, C-8 ), 1.14-1.28 (m, 1 H, C-8 ), 1.02-1.11 (m, 1 H, C-15 ), 0.72-0.87 (m, 1 H, C-18 ), 0.44-0.54 (m, 2 H, C-19 H, C-20 ), 0.04-0.12 (m, 2 H, C-19 H', C-20 H'). organic fractions were washed with H20 (15 mL), and removal of solvent by evaporation yielded a viscous burgundy oil which was purified by flash column chromatography.…”
Section: -(Cyclopropylmethyl)-45a-epoxy-6/s-[[3-(isothiocyanatomethyl...mentioning
confidence: 99%
See 2 more Smart Citations
“…After conditioning the silica gel with CH2Cl2 (100 mL), the residue was eluted sequentially with CH2CI2 (150 mL), 80:20 CH2Cl2:EtOAc (300 mL), and 50:50 CH2Cl2:EtOAc (200 mL). The product was eluted with the second eluent mixture, and removed of solvent by rotary evaporation afforded 20 as a yellow foam (390 mg, 63% yield): NMR (CDCls) ó 8.03 (d, J = 8.2 Hz, 1 H, C-24 H), 7.98 (d, J = 8.2 Hz, 1 H, C-27 H), 7.52 (dd, J = 7.6, 7.6 Hz, 1 H, C-26 H), 7.39-7.47 (m, 6 H, C-23' 3 H, C-27' 3 H), 7.33 (dd, J = 7.8, 7.8 Hz, 1 H, C-25 ), 7.12-7.26 (m, 9 H, C-24' 3 H, C-25' 3 H, C-26' 3 H), 6.47 (d, J = 8.2 Hz, 1 H, C-2 H), 6.22 (d, J = 8.3 Hz, 1 H, C-l ), 5.09 (d, J = 15.5 Hz, 1 H, C-21 H), 5.01 (d, J = 15.2 Hz, 1 H, C-21 H), 4.45 (d, J = 6.4 Hz, 1 H, C-5/3 ), 3.10-3.22 (m, 1 H, C-6a H), 2.99 (d, J = 4.9 Hz, 1 H, C-9 H), 2.86 (d, J = 18.6 Hz, 1 H, C-10/3 H), 2.37-2.55 (m, 2 H, C-lOa H, C-16 H), 2.29 (d, J = 6.5 Hz, 2 H, C-17 2 ), 1.72-2.12 (m, 4 H, C-7 2 H, C-15 H, C-16 ), 1.48-1.59 (m, 1 H, C-8 ), 1.14-1.28 (m, 1 H, C-8 ), 1.02-1.11 (m, 1 H, C-15 ), 0.72-0.87 (m, 1 H, C-18 ), 0.44-0.54 (m, 2 H, C-19 H, C-20 ), 0.04-0.12 (m, 2 H, C-19 H', C-20 H'). organic fractions were washed with H20 (15 mL), and removal of solvent by evaporation yielded a viscous burgundy oil which was purified by flash column chromatography.…”
Section: -(Cyclopropylmethyl)-45a-epoxy-6/s-[[3-(isothiocyanatomethyl...mentioning
confidence: 99%
“…Structural modification of naltrexone has shown that C-6 substitution, even with relatively large substituents, affords potent agents. Some examples include 6-desoxy-6-methylenenaltrexone (nalmefene (2) and 6/3-methyl-6a-naltrexol (3), which are potent opioid antagonist,1 and compounds with even larger substituents attached at the C-6 position, such as /3-chlomaltrexamine (/3-CNA) (4) and /3-funaltrexamine (/3-FNA) (5), which are important electrophilic ligands. 2 The C-6 position has served as the location for a variety of substituents which have led to several derivatives of the 6/3-and 6a-amines, including amides as conjugate addition acceptors, thiol reagents, and -haloacetamides.…”
mentioning
confidence: 99%
See 1 more Smart Citation